Новітні системи виявлення вторгнень і керований захист в хмарній інфраструктурі - Белозьоров, С. Ю. (ХНУРЕ, 2023)
The presented work is devoted to the analysis of modem intmsion detection systems and managed information protection in cloud infrastmctures. Google Corporation has developed Cloud IDS intrusion detection system for its GCP cloud technologies. This system provides detection of intrusion threats, malware, spyware, and command attacks on the network. Peer-to-peer traffic is mirrored and then inspected by Palo Alto Networks threat protection technologies. To act against threats detected by Cloud IDS, Google developed the Google Cloud Armor system.